2011
DOI: 10.1080/09064702.2011.560179
|View full text |Cite
|
Sign up to set email alerts
|

Silage-concentrate finishing of bulls versus silage or fresh forage finishing of steers: Effects on fatty acids and meat tenderness

Abstract: The objective of this trial was to assess meat quality in terms of tenderness and fatty acid (FA) composition in M. longissimus dorsi and M. gluteus medius from bulls finished on ad lib silage-concentrates (SIL:CON) vs. steers fed ad lib silage (FF) or restricted silage and unrestricted grazing (RES-F). Warner-Brazler shear force value day 1 was lowest for the FF steers (pB0.05). Myofibril fragmentation index (MFI) values were similar after seven days of ageing, showing that ageing compensated for differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…The n-6/n-3 ratio at the C18 chain length was at the same level as found by Moloney et al (2013) in heifers finished at a similar diet, and the total n-6/n-3 ratio over all chain lengths (C18, C20 and C22) were at the same low level as found for pasture-derived label beef of calves, heifers and steers by Razminowicz et al (2006) and in forage-fed steers by Turner et al (2011). Significantly lower proportions of long-chain n-6 PUFA (P = 0.03), as well as long-chain n-3 PUFA (P = 0.01), with increasing IMF on muscle basis might be caused by the higher phospholipid proportions in IMF in leaner bulls (Wood et al, 2008).…”
Section: Fatty Acid Profile Of Imf and Fatty Acid Concentrations In Musclesupporting
confidence: 65%
“…The n-6/n-3 ratio at the C18 chain length was at the same level as found by Moloney et al (2013) in heifers finished at a similar diet, and the total n-6/n-3 ratio over all chain lengths (C18, C20 and C22) were at the same low level as found for pasture-derived label beef of calves, heifers and steers by Razminowicz et al (2006) and in forage-fed steers by Turner et al (2011). Significantly lower proportions of long-chain n-6 PUFA (P = 0.03), as well as long-chain n-3 PUFA (P = 0.01), with increasing IMF on muscle basis might be caused by the higher phospholipid proportions in IMF in leaner bulls (Wood et al, 2008).…”
Section: Fatty Acid Profile Of Imf and Fatty Acid Concentrations In Musclesupporting
confidence: 65%
“…The results are shown in Table 1. [27][28][29], crops [30,31], plant oil [32,33], shellfish [34], fish [34][35][36][37][38][39][40], meat [41][42][43][44][45][46][47][48][49][50][51][52][53], and dairy products [54][55][56][57] 2 IA Index of atherogenicity [C12:0 + (4 × C14:0) + C16:0]/ΣUFA Seaweeds [27][28][29]58,59], crops [30,31,60,61], plant oil [33,62], shellfish [63], shrimp [64], fish [36][37][38][39][65]…”
Section: Nutritional Indicesmentioning
confidence: 99%
“…The carcasses lost on average 1.7% water during the 48 h of refrigeration, but no difference in chilling losses was found between treatments (P 0.10; Table 3). Turner et al (2011) reported no difference in final liveweight of steers fed barley supplements as a TNC source during the finishing period as opposed to steers finished on a silage diet. However, unlike the present study, Turner et al (2011) observed a difference in carcass yield, possibly due to the age at slaughter, which differed between the two studies (approximately 1 vs. 2 yr old).…”
Section: Carcass Quality Characteristicsmentioning
confidence: 95%
“…Turner et al (2011) reported no difference in final liveweight of steers fed barley supplements as a TNC source during the finishing period as opposed to steers finished on a silage diet. However, unlike the present study, Turner et al (2011) observed a difference in carcass yield, possibly due to the age at slaughter, which differed between the two studies (approximately 1 vs. 2 yr old). Nevertheless, as far as the carcass cuts (LT and ST) weight is concerned, the present results are in agreement with those of del Campo et al (2008), who reported no differences in striploin, tenderloin and rump weights for steers fed either pasture or pasture and corn as a source of TNC.…”
Section: Carcass Quality Characteristicsmentioning
confidence: 95%